PKM Pelatihan Dan Penerapan Budidaya Tanaman Secara Hidroponik Pada Kelompok PKK (KWT) Desa Sei Rotan Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Asmah Indrawati; Rizal Aziz; Mitra Musika Lubis; Muhammad Usman (Universitas Medan Area, 2022)
Efforts to increase the income of the PKK KWT group in Sei Rotan village are carried out by the Tridarma activity of higher education. The objectives of the service activities include increasing efforts to maximize house yard land management efforts by cultivating horticultural plants in the yard, and increasing the knowledge, understanding and skills of the community on hydrophonic plant cultivation techniques in the PKK KWT group community, Sei Rattan Village, Percut Sei Tuan District, and to improve community income which is classified as fitting to meet daily life, the implementation method applied is by conducting training and mentoring, in the training activities training is carried out: Hydrophonic Cultivation Training vertically and horizontally, Technical culture training for HEALTHY Horticulture plants through hydrophonic seeds, while in Mentoring: Guidance and Community Development who have started to apply technology, Discussion and Evaluation. the results of the activities based on the transfer of knowledge obtained a statement 60% of the community's responses strongly agree, 30% agree, increasing community knowledge after training obtained very good data 25%, good 60% and good enough 9%, and not good 0% and responses Satisfaction with PKM activities shows the data is very useful 42% and useful 52% and quite useful 2% and 0% which states not useful. The three categories of community responses show that the activities that have been carried out show that it is very important for the community to consider community knowledge and skills that are very useful for improving the quality of these farmer groups.